Regions. Peripheries and centres. Networks of cities. PB Discussion Club - Bokov, Andrey; Gimelshteyn, Alexander; Grigoryeva, Elena; Lidin, Konstantin; Makarov, Andrey; Mayarenkov, Sergey; Surikova, Evgeniya (project baikal, 2023)
On February 7, a discussion club of PB was held in the Irkutsk House of Architects. It was devoted to the theme of the current issue, “Regions. Peripheries and Centres”. The round table brought together academician Andrey Bokov, historian and publisher Alexander Gimelshteyn, architect and publisher Elena Grigoryeva, architect Andrey Makarov and businessman Sergey Mayarenkov. Konstantin Lidin was its moderator.